2008
DOI: 10.1108/13555850810844869
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analytic hierarchy process and entropy to develop a durable goods chain store franchisee selection model

Abstract: Purpose -The purpose of this paper is to present a selection model that adopts several important criteria, enabling a durable goods franchiser to select franchisees that are most appropriate. Design/methodology/approach -Questionnaires based on selection criteria are identified from modified Delphi Technique and then sent to experts and decision makers. Major criteria weights are analyzed using the analytic hierarchy process and entropy. Final weights are then determined using the compromised weighting method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In spite of its importance, literature on franchising continues to be incomplete and partial. While previous studies have identified the partner selection criteria employed and the process utilised to select franchise partners (Jambulingam and Nevin, 1999; Choo et al , 2007; Clarkin and Swavely, 2006; Doherty, 2009; Hsu and Chen, 2008), these studies were all carried out from the viewpoint of the franchisor only, ignoring the views of the other important player, the franchisee.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of its importance, literature on franchising continues to be incomplete and partial. While previous studies have identified the partner selection criteria employed and the process utilised to select franchise partners (Jambulingam and Nevin, 1999; Choo et al , 2007; Clarkin and Swavely, 2006; Doherty, 2009; Hsu and Chen, 2008), these studies were all carried out from the viewpoint of the franchisor only, ignoring the views of the other important player, the franchisee.…”
Section: Discussionmentioning
confidence: 99%
“…Clarkin and Swavely's (2006) study of 1,043 multi sector North American franchisors identified the importance of franchisees' personal characteristics, including financial strength, attitudes and personality, psychological profiling, formal education, general business and industry specific experience. Similarly, Hsu and Chen (2008) identified the operating ability, financial capability, experience and personality as selection criteria for retail franchisors in Taiwan. The authors conclude however, that financial and business ability are the key traits for franchisors to determine.…”
Section: Partner Selectionmentioning
confidence: 99%
“…Thus, [according to the scales of the proper selection (Jambulingam and Nevin, 1999), the evaluation of the financial stability, attitude and personal properties of the license-receivers (Doherty and Alexander, 2004), paying of attention to the attitude and personality (Clarkin and Swavely, 2006), consideration of the traditional scales (Jambulingan and Nevin, 1999), paying of attention to the financial power, access to the landed properties and estates as well as local knowledge (Clarkin and Swavely, 2007), financial and business ability (Hsu and Chen, 2008), selection of a common investing partner (Geringer, 1991)], it can be concluded that the results and subject discussed in the aforementioned researches point to the agency-granting systems and no work has considered the details of selecting an appropriate business partner (license receiver) and designed a pattern for the selection of the business partner (license receiver). This research codifies the scales related to business partners as well as the criteria pertinent to duty with an approach to network division in the selection of the business partner with the least error in the selection of business partner in the agency-granting systems.…”
Section: Discussionmentioning
confidence: 99%
“…al 2011 and appropriate financial background were found to be among the most relevant hard and soft facts (Doherty 2009, Rahatullah and Raeside 2009, Clarkin and Swavely 2006, Olm et. al 1988, DeCeglie 1993, Hsu and Chen 2008. Also education (Doherty 2009, Clarkin and Swavely 2006, DeCeglie 1993, and experience (Hsu and Chen 2008, Clarkin and Swavely 2006, McCosker 2000 are often rated highly towards a fitting candidate profile.…”
mentioning
confidence: 99%
“…al 1988, DeCeglie 1993, Hsu and Chen 2008. Also education (Doherty 2009, Clarkin and Swavely 2006, DeCeglie 1993, and experience (Hsu and Chen 2008, Clarkin and Swavely 2006, McCosker 2000 are often rated highly towards a fitting candidate profile. As per definition soft skills are generally referred to customer handling, communication, problem solving, teamworking, loyalty, enthusiams, punctuality, and strong work ethics (Oxford Reference online).…”
mentioning
confidence: 99%